2004
DOI: 10.1523/jneurosci.1422-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Natural Stimulus Statistics Alter the Receptive Field Structure of V1 Neurons

Abstract: Studies of the primary visual cortex (V1) have produced models that account for neuronal responses to synthetic stimuli such as sinusoidal gratings. Little is known about how these models generalize to activity during natural vision. We recorded neural responses in area V1 of awake macaques to a stimulus with natural spatiotemporal statistics and to a dynamic grating sequence stimulus. We fit nonlinear receptive field models using each of these data sets and compared how well they predicted time-varying respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
304
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(327 citation statements)
references
References 52 publications
17
304
2
Order By: Relevance
“…These stimuli mimicked the stimulation occurring in an area three to four times the CRF diameter during inspection of a natural scene with voluntary eye movements (Vinje & Gallant 2000;David et al 2004). A brief segment taken from a natural vision movie appears at the top of Figure 1A.…”
Section: Natural Vision Moviesmentioning
confidence: 99%
See 1 more Smart Citation
“…These stimuli mimicked the stimulation occurring in an area three to four times the CRF diameter during inspection of a natural scene with voluntary eye movements (Vinje & Gallant 2000;David et al 2004). A brief segment taken from a natural vision movie appears at the top of Figure 1A.…”
Section: Natural Vision Moviesmentioning
confidence: 99%
“…At the same time, functional models of visual neurons have been developed largely using simple synthetic stimuli, such as bars, sine wave gratings and white noise (Hubel & Wiesel 1959;DeValois et al 1982;Jones et al 1987). The question of how well models developed using synthetic stimuli generalize to natural vision has received little attention (Vinje & Gallant 1998;David et al 2004). This is an issue of fundamental importance for understanding visual processing.…”
Section: Introductionmentioning
confidence: 99%
“…If V1 neurons were linear filters, this would not be the case; RF models would generalise between classes of stimuli. So the stimulus specificity of RF predictions that David et al (2004) report, which seem to be due to crucial nonlinearities in V1, again points to a more dynamic notion of RF than was originally conceived.…”
Section: Natural Imagesmentioning
confidence: 76%
“…Two studies (Ringach, Hawken & Shapley 2002, Smyth, Willmore, Baker, Thompson & Tolhurst 2003 have shown that receptive field maps generated from responses to natural images resemble the elongated, oriented fields derived from the classic grating experiments. In contrast, David, Vinje and Gallant (2004) have made the case that RF models generated by stimulation with natural stimuli give significantly better predictions of responses to novel natural stimuli than do RF models generated by stimulation with gratings. Likewise, the predictions of responses to novel grating stimuli were superior if the RF model had been constructed from the correlations of responses to gratings.…”
Section: Natural Imagesmentioning
confidence: 99%
See 1 more Smart Citation